Developing Social Distance Awareness during Pandemic Covid-19 Pandemic Through Interactive Video for Community in DKI Jakarta - Herawaty Br Dalimunthe, Henny; Hadiyanti, Puji; Tijari, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
The COVID-19 pandemic situation faced by the people of Indonesia an impact in various fields of economy, education, and health. Pandemic conditions require people to stay at home to break the chain of viruses spreading rapidly. Basic education to higher education runs online learning so that learning continues. Through the Real Work Lecture Program (KKN) involving students and community participation to help break the chain of distribution with online fig. Public awareness methods with socialization, counseling, online empowerment using interactive video media that can be accessed on YouTube, WA group, online newspapers, and placing posters and banners in strategic locations so that they can be seen, read, and remembered by the public. The results of this activity can have a good impact on the community to break the chain of the spread of COVID-19 practically, easy to access using communication tools (HP) and socialization which is carried out close to people's lives.